PERFORMANCE PARTAI POLITIK DALAM PANGGUNG PILKADA JAWA TIMUR - Rolis, Moh. Ilyas (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article aims to describe the performance of political parties in pilkada. Pilkada as an integral part of local government system is expected to accelerate the ripening process of democracy in local level. In the event of elections (pilkada), political parties in a hurry and prioritize the aspects of winning candidates and provide tickets for candidates who have a chance to win. This article focused to describe the phenomenon of “the big man” at local elite’s recrutmen whom have a big social capital. This phenomena minimize local elites in local politic and creates political transaction in local politics. The findings indicate that political party has been part of this phenomenon.